‘Dignified’: An Exegetical Soteriology of Divine Honour - Borges, Jason (Scottish journal of theology, 2013)
Social scientists in disparate fields are now employing the construct of honour to ameliorate various social problems, such as immorality, failed states, international discord, poverty and mental illness. Moreover, historians of global religion cite Christianity's shift towards cultures shaped by the values of honour and shame. Despite this growing prominence of honour in social theories and the emergence of Christianity in honour–shame cultures, the notion of honour remains absent from theological discourse. In light of these global realities, we explore how God's active transformation of humanity from shame to honour can interpret both salvation-history and Christian theology. To this end I first explore the nature of humanity's problem of shame before God, using anthropological and biblical insights. Throughout the Old Testament, God's covenant initiatives with Abram, Moses and David, along with the common socio-literary pattern of God exalting a servant from unjust shame, reveals the dignified status God intends for humanity. God's programme to restore people from shame to honour climaxes in Jesus, who embodies honour in the incarnation, mediates dignity to the marginalised by healings and public fellowship, elaborates God's new code of honour which reinterprets social stigmas, and procures an exalted status for all peoples by atoning for shame and resurrecting to exaltation. Romans and 1 Peter are interpreted in their socio-historic contexts as apostolic instruments which expound the social implications of God's honour code. To unify the fractured Romans for the upcoming Spanish mission, Paul confronts social imperialism by replacing false honour claims with God's status now available by faith through grace in Christ. Meanwhile, 1 Peter assures maligned Christians of their exalted status and outlines honourable social relations. Then, in closing, we examine a soteriology of honour diachronically and systematically. In particular, how: biblical metaphors symbolise believers’ status transposition, group incorporation is key to New Testament soteriology, Eastern Orthodoxy's doctrine of theosis articulates the infusion of divine status, and other theological categories could be interpreted through honour-shame social values. These reflections towards an exegetical soteriology of divine honour are offered as an initial theological platform for addressing social issues where honour values prevail.